2013
DOI: 10.1071/rdv25n1ab100
|View full text |Cite
|
Sign up to set email alerts
|

100 Bovine Pregnancy-Associated Glycoproteins Are Allocated to Cotyledonary or Intercotyledonary Trophoblast According to Their Phylogenetic Origin

Abstract: The pregnancy-associated glycoproteins (PAG) form a multigenic family of aspartic peptidases specifically expressed within the trophoblast of the ruminant placenta. In Bos taurus, this family is composed of 21 members segregated into 2 phylogenetic groups. The PAG are mainly produced by the cotyledons, which are discrete areas of massive interdigitations between the maternal endometrium and the foetal trophoblast. Cotyledons are separated by the flat cell layer of intercotyledonary trophoblast areas. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although molecularly true, dissecting the discs to define the developmental stages of elongating conceptuses provides an advantage: knowing whether the conceptus is fully developed (elongation and gastrulation) or not. So far, molecular studies on bovine elongating conceptuses have identified gene clusters involved in cell growth and differentiation, connective tissue development, lipid metabolism, signaling pathways involving growth factors or cytokines and their receptors, as well as transcription factors (33,48,68,69).…”
mentioning
confidence: 99%
“…Although molecularly true, dissecting the discs to define the developmental stages of elongating conceptuses provides an advantage: knowing whether the conceptus is fully developed (elongation and gastrulation) or not. So far, molecular studies on bovine elongating conceptuses have identified gene clusters involved in cell growth and differentiation, connective tissue development, lipid metabolism, signaling pathways involving growth factors or cytokines and their receptors, as well as transcription factors (33,48,68,69).…”
mentioning
confidence: 99%